ADVANCE CARE PLANNING AND PALLIATIVE CARE IN CHRONIC DISEASE SYMPTOM MANAGEMENT. Issue 2 (1st June 2013) - Kubokawa, N; Nishikawa, M; Yokoe, Y; Fukuda, K; Hattori, H; Yong-Jae, H; Miura, H; Endo, H; Nakashima, K
Abstract : Background: Opioids are important in symptom management of dyspnoea in chronic diseases, for example, chronic obstructive pulmonary disease (COPD). Existing literature indicates that in the absence of advance care planning (ACP) for end-of-life decisions, we should consider whether concomitant opioid use is appropriate. In Japan, the appropriate timing of ACP for dyspnoea symptom management in chronic diseases is poorly understood. Aim: The primary aim was to clarify whether ACP should be performed by the palliative care (PC) team concomitantly with morphine administration. The secondary aim was to clarify the opinion of home care support physicians on concomitant use of opioids and ACP. Methods: We investigated the level of ACP conducted by PC teams among patients who were using opioids. We conducted an inventory survey on the concomitant use of morphine and ACP among 220 doctors, including 147 home care support physicians. Results: ACP was conducted by PC teams for all patients who were using opioids. PC team members agreed to concomitantly perform ACP and opioid administration for dyspnoea in diseases such as COPD, 137 (62.3%) among 220 doctors, including 147 home care support physicians were agreed to. Discussion: In comparison with PC team members, the ratio of home care support physicians who advocated ACP concomitantly with morphine for dyspnoea was low. Conclusion: This study clarified the opinions of home care support physicians and PC team members on the concomitant use of opioids and ACP.